2009
DOI: 10.1111/j.1523-1739.2009.01258.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Climate‐Driven Bird Distribution Changes and Forecasted Conservation Conflicts in a Neotropical Savanna

Abstract: Climate-change scenarios project significant temperature changes for most of South America. We studied the potential impacts of predicted climate-driven change on the distribution and conservation of 26 broad-range birds from South America Cerrado biome (a savanna that also encompass tracts of grasslands and forests). We used 12 temperature or precipitation-related bioclimatic variables, nine niche modeling techniques, three general circulation models, and two climate scenarios (for 2030, 2065, 2099) for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
80
0
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(102 citation statements)
references
References 54 publications
5
80
0
17
Order By: Relevance
“…These changes will lead to different patterns of HPAI H5N1 transmission and outbreaks among migratory birds. On one hand, due to more frequent winter mixing of migratory birds in traditional breeding and wintering areas (Hitch and Leberg, 2006;Marini et al, 2009), some species may change their role from long-to short-distance transmitters in new geographic areas. On the other hand, migration flyways may also be influenced by climate change, and new areas impacted by HPAI H5N1 outbreaks may emerge.…”
Section: Discussionmentioning
confidence: 99%
“…These changes will lead to different patterns of HPAI H5N1 transmission and outbreaks among migratory birds. On one hand, due to more frequent winter mixing of migratory birds in traditional breeding and wintering areas (Hitch and Leberg, 2006;Marini et al, 2009), some species may change their role from long-to short-distance transmitters in new geographic areas. On the other hand, migration flyways may also be influenced by climate change, and new areas impacted by HPAI H5N1 outbreaks may emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change has been suggested to reduce survival rates of Neotropical bird species (Blake & Loiselle 2015) and to reduce species richness and their current ranges both in the Atlantic Forest (Anciães & Peterson 2006) and Cerrado (Marini et al 2009), as well as in several other regions in the planet (Şekercioğlu et al 2012). Although the effects of climate change on species richness composition between periods must be considered, due to lack of detailed surveying methods during the 1800s, we cannot account for climatic changes on bird communities.…”
Section: Climate Changementioning
confidence: 99%
“…In some cases, models suggest that protected areas may no longer maintain populations of key species, possibly the very ones that the reserves were created to protect (Araújo et al, 2004). Thorn et al (2009) and Marini et al (2009b) have also reported its usefulness in targeting conservation efforts for threatened species. Conversely, shrinking distributions and range shifts could create new refugiaareas where threatened species would be concentrated in the future (Loarie et al, 2009).…”
Section: Introductionmentioning
confidence: 99%